2020
DOI: 10.1111/cmi.13181
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B subviral envelope particles use the COPII machinery for intracellular transport via selective exploitation of Sec24A and Sec23B

Abstract: Hepatitis B virus (HBV) is a leading cause of liver disease. Its success as a human pathogen is related to the immense production of subviral envelope particles (SVPs) contributing to viral persistence by interfering with immune functions. To explore cellular pathways involved in SVP formation and egress, we investigated hostpathogen interactions. Yeast-based proteomics revealed Sec24A, a component of the coat protein complex II (COPII), as an interaction partner of the HBV envelope S domain. To understand how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…An increasing number of studies have reported that the ER-derived COPII-coated vesicles, which bud at the ER exit site (ERES), are redirected away from the Golgi and toward the nascent phagophore, thereby contributing to autophagosome formation in both yeast and mammalian cells [54][55][56]. A recent study by Zeyen et al has found that the HBV envelope selectively encounters the SEC24A/SEC23B complex in COPII vesicles through a direct interaction involving the N-terminal of SEC24A and a di-arginine motif of its S domain, indicating that viral envelope coating in COPII vesicles serves an important source of autophagy mediated-HBV envelope formation [57]. Therefore, autophagosomes and other autophagic compartments provide a physical scaffold for HBV envelopment and serve as a source of viral envelope membranes.…”
Section: Hbv Utilizes Autophagic Elements For Its Envelopmentmentioning
confidence: 99%
“…An increasing number of studies have reported that the ER-derived COPII-coated vesicles, which bud at the ER exit site (ERES), are redirected away from the Golgi and toward the nascent phagophore, thereby contributing to autophagosome formation in both yeast and mammalian cells [54][55][56]. A recent study by Zeyen et al has found that the HBV envelope selectively encounters the SEC24A/SEC23B complex in COPII vesicles through a direct interaction involving the N-terminal of SEC24A and a di-arginine motif of its S domain, indicating that viral envelope coating in COPII vesicles serves an important source of autophagy mediated-HBV envelope formation [57]. Therefore, autophagosomes and other autophagic compartments provide a physical scaffold for HBV envelopment and serve as a source of viral envelope membranes.…”
Section: Hbv Utilizes Autophagic Elements For Its Envelopmentmentioning
confidence: 99%
“…These particles, also referred to as hepatitis B surface antigen (HBsAg) particles, are secreted in extreme surplus compared to the infectious HBV particles and are thought to act as decoys to the immune system [26,27]. The viral S envelope protein alone is sufficient for the production of spherical SVPs with diameters of about 22 nm that are formed by self-assembly of about 100 S molecules in the ER-Golgi intermediate compartment (ERGIC) and are released via the constitutive pathway of secretion [28,29]. Remarkably, the budding and secretion of spherical SVPs does neither require N146-linked glycans [11,13,14] nor ESCRTs [21,23], implicating that HBV exploits distinct cellular pathways and host factors to release its particle types.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for host factors involved in HBV particle-type exports, we recently employed yeast-based proteomics and identified Sec24A as an interaction partner of the HBV envelope S domain [29]. Sec24 is the cargo adaptor of the coat protein complex II (COPII), a vesicular transport machinery that moves selected secretory cargos from the ER to the Golgi apparatus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This organelle occupies a significant volume in many cell types, and, as such, is a natural target for exploitation by viruses that need a source of membranes for their assembly in infected cells. Indeed, recent articles have highlighted that not only is it the ER membrane that is used by viruses, but that, in fact, certain viruses such as hepatitis B [17] and rotavirus [18] specifically subvert the ER export machinery, as discussed in [3], to their ends. Arakawa and Morita provide a detailed review of how the ER is used as a replication organelle for the flaviviruses, a group that includes the dengue, Zika and tick-borne encephalitis viruses, among others [5].…”
mentioning
confidence: 99%